Challenges to accessing crucial services in the management of children having Autism Spectrum Disorders: Caregivers' perspective in Kenya - Evans Obara Obaigwa; Lizahn Gracia Cloete (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2019)
Background and introduction: Autism Spectrum Disorder is a global public health concern which has attracted little attention from African countries such as Kenya. As a result, children with ASD and their caregivers are facing significant barriers to accessing crucial services compared with the general population.  Methodology: A qualitative, descriptive phenomenological study utilizing Focus Group Discussions (FGDs) was conducted. Analysis: The data was transcribed verbatim before QSR N'Vivo 10 was used to organize and analyze the data from transcripts of field notes and interviews. Content analysis was used to identify important ideas and concepts. Findings: One theme, namely, "the burden of caring for children with ASD" was identified. Implications and recommendations: Occupational therapists and other relevant stakeholders should provide accessible services that will promote the quality of life for children with ASD and their caregivers in Kenya.